Vitiligo and Autoimmune Thyroid Disorders - Baldini, Enke; Odorisio, Teresa; Sorrenti, Salvatore; Catania, Antonio; Tartaglia, Francesco; Carbotta, Giovanni; Pironi, Daniele; Rendina, Roberta; D’Armiento, Eleonora; Persechino, Severino; Ulisse, Salvatore (Frontiers in Endocrinology, 2017)
Vitiligo represents the most common cause of acquired skin, hair and oral depigmentation, affecting 0.5-1% of the population worldwide. It is clinically characterized by the appearance of disfiguring circumscribed skin macules following melanocyte destruction by autoreactive cytotoxic T lymphocytes. Patients affected by vitiligo usually show a poorer quality of life and are more likely to suffer from depressive symptoms, particularly evident in dark-skinned individuals. Although vitiligo is a non-fatal disease, exposure of affected skin to UV light increases the chance of skin irritation and predisposes to skin cancer. In addition, vitiligo has been associated to other rare systemic disorders due to the presence of melanocytes in other body districts, such as in eyes, auditory, nervous and cardiac tissues, where melanocytes are thought to have roles different from that played in the skin. Several pathogenetic models have been proposed to explain vitiligo onset and progression, but clinical and experimental findings point mainly to the autoimmune hypothesis as the most qualified one. In this context, it is of relevance the strong association of vitiligo with other autoimmune diseases, in particular with autoimmune thyroid disorders, such as Hashimoto thyroiditis and Graves’ disease. In this review, after a brief overview of vitiligo and its pathogenesis, we will describe the clinical association between vitiligo and autoimmune thyroid disorders and discuss the possible underlying molecular mechanism(s).